1995
DOI: 10.1063/1.114353
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between self-organization and size of InAs islands on InP(001) grown by gas-source molecular beam epitaxy

Abstract: Using the strained-induced 2D–3D transition, InAs dots have been grown on InP(001) and examined by transmission electron microscopy. Two different modes of island size and spatial distribution have been identified. For deposit of 1.5 and 1.8 monolayers, the islands are about 7 nm high and randomly distributed. Above 2 monolayers, they are about five times smaller in volume and locally self-organized, with a typical distance of 40 nm independent of the island density. It is suggested that the strong dependence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(71 citation statements)
references
References 0 publications
6
63
2
Order By: Relevance
“…However, the 3.2% mismatch between InAs and InP lattice parameters leads to a transition from a two dimensional (2D) to a three dimensional (3D) growth mode between 2 and 3 ML. 12,13 We have shown that Sb surfactant mediated growth prevents InAs 3D growth up to 14 ML on Ga 0.47 In 0.53 As matrix.…”
Section: 9mentioning
confidence: 99%
“…However, the 3.2% mismatch between InAs and InP lattice parameters leads to a transition from a two dimensional (2D) to a three dimensional (3D) growth mode between 2 and 3 ML. 12,13 We have shown that Sb surfactant mediated growth prevents InAs 3D growth up to 14 ML on Ga 0.47 In 0.53 As matrix.…”
Section: 9mentioning
confidence: 99%
“…Growth conditions (e.g., the influence of group V pressure, substrate temperature, and growth procedure without or with growth interruption during InAs delivery) employed for the formation of InAs 3D islands have been carefully examined. 52,53,67,75,76,77,78,79 The kinetic processes impacting the evolution of semiconductor 3D islands and their size distribution are two subjects highly relevant to envisioning practical implementation of ensembles of semiconductor 3D islands as an active or a passive part in solid-state devices Therefore, systematic study, using in situ ultrahigh vacuum (UHV) atomic force microscope (AFM) and scanning tunneling microscope (STM), on the growth of InAs 3D islands on GaAs(001) surfaces is essential. The unique evolution of InAs 3D islands at sequential growth stages characterized by specific InAs coverage is described in the following section with the aim at minimizing size distribution of an ensemble of InAs 3D islands.…”
Section: Lateral Size Equalizationmentioning
confidence: 99%
“…9 However, InAs islands made on (001) and on (113)B substrates demonstrate facets of different crystallographic orientations. InAs islands formed on InP (001) substrates show highindex facets like (114), 27,28 while the islands obtained on (113)B substrates are found to have low-index facets in {001}{110} and {111} families. 29,30 If we assume that the adsorption of Sb noticeably reduces the surface energy of low-index facets like (001), (110), or (111) while it reduces the high-index ones like {113} or {114} to a smaller extent or even increases their energies, the drastically different effects of Sb versus substrate orientations observed can then be explained ( Figure 5).…”
mentioning
confidence: 99%